ARE THE SOLUTIONS OF STRESS INVERSION CORRECT? VISUALIZATION OF THEIR RELIABILITY AND THE SEPARATION OF STRESSES FROM HETEROGENEOUS FAULT-SLIP DATA - Yamaji A. (My University, 2003)
It is now a conventional technique to determine the optimal stress from fault-slip data by inversion. However, the method is weak when applied to heterogeneous data. A new technique is presented here to visualize the reliability of the solution. It is also shown that the technique allows us to separate stresses from those data. The technique is simple: it is the visualization of the object function of the inversion. The present method is compared with the conventional inverse method and the multi-inverse method using artificial and natural heterogeneous data sets. The conventional method can determine one of the stresses, if the orientation of the faults has a large variation. It is shown that the solutions of the method are non-unique and unstable for some data sets, indicating that they are not reliable. The present graphical method and multi-inverse method are more robust than the conventional one for heterogeneity. The multi-inverse method seems to have better resolution than the present method. However, unlike the multi-inverse method, the time of computation of the present method does not increase with the number of faults, so that the method becomes favorable for processing hundreds of faults.
Keywords: STRESS INVERSION; FAULT SLIP DATA; POLYPHASE TECTONICS; TECTONIC STRESS